Mind the gap (junction): cGMP induced by nitric oxide in cardiac myocytes originates from cardiac fibroblasts. (27th December 2019) - Menges, Lukas; Krawutschke, Christian; Füchtbauer, Ernst‐Martin; Füchtbauer, Annette; Sandner, Peter; Koesling, Doris; Russwurm, Michael
Abstract : Background and Purpose: The intracellular signalling molecule cGMP, formed by NO‐sensitive GC (NO–GC), has an established function in the vascular system. Despite numerous reports about NO‐induced cGMP effects in the heart, the underlying cGMP signals are poorly characterized. Experimental Approach: Therefore, we analysed cGMP signals in cardiac myocytes and fibroblasts isolated from knock‐in mice expressing a FRET‐based cGMP indicator. Key Results: Whereas in cardiac myocytes, none of the known NO–GC‐activating substances (NO, GC activators, and GC stimulators) increased cGMP even in the presence of PDE inhibitors, they induced substantial cGMP increases in cardiac fibroblasts. As cardiac myocytes and fibroblasts are electrically connected via gap junctions, we asked whether cGMP can take the same route. Indeed, in cardiomyocytes co‐cultured on cardiac fibroblasts, NO‐induced cGMP signals were detectable, and two groups of unrelated gap junction inhibitors abolished these signals. Conclusion and Implication: We conclude that NO‐induced cGMP formed in cardiac fibroblasts enters cardiac myocytes via gap junctions thereby turning cGMP into an intercellular signalling molecule. The findings shed new light on NO/cGMP signalling in the heart and will potentially broaden therapeutic opportunities for cardiac disease.